Matka odchodzi Tadeusza Różewicza jako asamblaż narracyjny: - - Paczkowski, Mikołaj (Zagadnienia Rodzajów Literackich, 2019)
This work is an attempt at reading Tadeusz Różewicz’s book entitled Mother Departs from the perspective of literary genetics. A literary genre has been treated as a factor in the interpretation, which could influence the reception of the text. The first part concerns proposals indicated by scholars and critics in the context of this work, such as the Lament, the Treaty of poetry, collage or silva. In the second part the interpretation was carried out taking into account the author’s concept of genre, which is narrative Assemblage Art.